2014
DOI: 10.1007/s00296-014-3056-5
|View full text |Cite
|
Sign up to set email alerts
|

Baseline serum interleukin-34 levels independently predict radiographic progression in patients with rheumatoid arthritis

Abstract: The aim of our observational study was to investigate the clinical significance of interleukin (IL)-34, a novel osteoclastogenic cytokine, for predicting structural damage in patients with rheumatoid arthritis (RA). Serum IL-34 levels were measured in 100 RA patients, 36 patients with ankylosing spondylitis (AS), and 59 gender- and age-matched healthy individuals using an enzyme-linked immunosorbent assay. We also measured IL-34 concentrations in synovial fluid (SF) samples from 18 RA patients and 19 osteoarth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
25
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 30 publications
10
25
0
1
Order By: Relevance
“…This was in accordance with a recent study by Chang et al that baseline IL-34 levels were positively correlated to ΔSHS/year [49]. As it was previously confirmed that SHS was positively correlated with disease activity and local inflammation and this was similar to our findings [50].…”
Section: Discussionsupporting
confidence: 83%
“…This was in accordance with a recent study by Chang et al that baseline IL-34 levels were positively correlated to ΔSHS/year [49]. As it was previously confirmed that SHS was positively correlated with disease activity and local inflammation and this was similar to our findings [50].…”
Section: Discussionsupporting
confidence: 83%
“…With regard to experimental arthritis, it is interesting to note that the lack/blockade of CSF-1 as well as the blockade of CSF-1R is associated with less severe methylated bovine serum albumin (mBSA)-induced arthritis and CIA [146][147][148]. In RA patients, all available studies pointed to increased serum and SF levels of IL-34 with respect to normal and disease controls (OA, PsA, ankylosing spondylitis (AS)) [149][150][151][152][153]. Of interest, ser0075m IL-34 levels correlated with immunological markers of more severe disease including rheumatoid factor (RF), anticyclic citrullinated peptide antibody (anti-CCP) titers, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and with disease activity and smoking [149][150][151][152].…”
Section: Il-34mentioning
confidence: 99%
“…In RA patients, all available studies pointed to increased serum and SF levels of IL-34 with respect to normal and disease controls (OA, PsA, ankylosing spondylitis (AS)) [149][150][151][152][153]. Of interest, ser0075m IL-34 levels correlated with immunological markers of more severe disease including rheumatoid factor (RF), anticyclic citrullinated peptide antibody (anti-CCP) titers, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and with disease activity and smoking [149][150][151][152]. In this regard, serum IL-34 levels have been also associated with radiographic progression and appear to be good predictors of radiographic damage in RA patients [150,152].…”
Section: Il-34mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported 1,5 that elevated levels of IL-34 have been observed in the joint tissue, serum, synovial fluid, and fibroblast-like synoviocytes of patients with RA. Interestingly, elevated levels of IL-34 were also detected in early RA (disease duration ≤ 6 mos) 2 and a significant association was found between IL-34 expression and synovitis severity 6 . Of greatest interest, significant positive correlations were found between IL-34 levels, inflammation variables (such as erythrocyte sedimentation rate and C-reactive protein), antibodies production (such as RF and anti-CCP), and disease activity indexes (such as tender joint count and the Disease Activity Score at 28 joints) 7 .…”
Section: To the Editormentioning
confidence: 97%